A DEIXIS ANALYSIS OF SONG LYRICS IN SAM SMITH’S “LOVE GOES” ALBUM - Syanti Dewi Lestari; Katharina Rustipa (Universitas Stikubank (UNISBANK) Semarang, 2022)
This study applies Yule's theory to evaluate the use of deixis in the lyrics of Sam Smith's song